Characteristics of Carbapenemase-Producing Klebsiella pneumoniae Isolated in the Intensive Care Unit of the Largest Tertiary Hospital in Bangladesh - Okanda, Takashi; Haque, Anwarul; Koshikawa, Takuro; Islam, Amirul; Huda, Qumrul; Takemura, Hiromu; Matsumoto, Tetsuya; Nakamura, Shigeki (Frontiers in Microbiology, 2021)
For addressing the issue of antimicrobial drug resistance in developing countries, it is important to investigate the characteristics of carbapenemase-producing Organisms. We aimed to genetically characterize a carbapenemase-producing Klebsiella pneumoniae (CPKP) isolated in the intensive care unit of a tertiary hospital in Bangladesh. The number of CPKP isolates were 43 (30%), of which pandrug-resistant (PDR) strains were 14%. These carbapenemases were NDM-1 (53%), NDM-5 (14%), OXA-181 (12%), OXA-232 (10%), NDM-5 + OXA-181 (5%), and NDM-5 + OXA-232 (2%). Many CPKP isolates harbored a variety of resistance genes, and prevalence of 16S rRNA methyltransferase was particularly high (91%). The 43 CPKP isolates were classified into 14 different STs, and the common STs were ST34 (26%), ST147 (16%), ST11 (9%), ST14 (9%), ST25 (7%), and ST231 (7%). In this study, PDR strains were of three types, ST147, ST231 and ST14, and their PDR rates were 57%, 33% and 25%, respectively. The spread of the antimicrobial drug resistance of CPKP in Bangladesh was identified. In particular, the emergence of PDR is problem, and there may be its spread as a superbug of antimicrobial treatment.